A REVIEW OF MORPHOMETRIC, X-RAY-ANATOMICAL, AND NEUROLOGICAL FEATURES OF CEREBRAL VENTRICLES IN CRANIAL INJURIES AND THEIR CLINICAL IMPLICATIONS - Yo’ldosheva Naima Qudratovna (TADQIQOTLAR.UZ, 2024)
Abstract Cranial  injuries  significantly  impact  the  structure  and  function  of  cerebral ventricles,  with  potential  long-term  consequences  on  neurological  health.  Ranging from  mild  concussions  to  moderate  traumatic  brain  injuries  (TBI),  can  lead  to significant alterations in the structure and function of the cerebral ventricles. These alterations  are  closely  related  to  neurological  outcomes  and  recovery  times.  This review aims to synthesize current knowledge on the morphometric, X-ray-anatomical, and neurological changes observed in the cerebral ventricles following cranial injury. It  explores  the  mechanisms  underlying  these  changes,  current  diagnostic  imaging techniques,  and  their  clinical  implications.  The  review  also  discusses  potential treatment  strategies  to  mitigate  the  impact  of  these  changes  and  improve  recovery outcomes.  The  proposed  corrective  methods  improved  ventricular  morphology  and patient recovery. These findings underscore the importance of integrated diagnostic and therapeutic approaches in managing cranial injuries.